Country Partnership Framework for the Republic of Chad for the Period FY16-20 - World Bank Group (World Bank, Washington, DC, 2016)
This Country Partnership Framework (CPF) is designed to support the forthcoming Chad Five-Year Development Plan (2016-2020). It succeeds the Interim Strategy agreed with the Government of Chad in March 2010. The Interim Strategy Note (ISN) set out the World Bank Group’s (WBG’s) support to Chad for the period 2010-2012. The strategy was composed of three main pillars: strengthening governance; improving livelihoods and access to key social services; and improving regional integration and connectivity. The WBG has continued to operate on the basis of the ISN since 2012, as the conditions were put in place for a return to a full partnership framework, in particular the full resumption of an IMF program and of the dialogue towards the HIPC Completion Point. In May 2013 the Government of Chad published its National Development Plan (NDP) for the period 2013-2015, which is considered the third Poverty Reduction Plan for Chad. This included a strong results framework, with 24 strategic indicators and 65 intermediary indicators, including all HIPC completion point triggers. It was the subject of a Joint Staff Advisory Note (JSAN) in June 2013 in which the WBG and IMF broadly endorsed the thrust of the plan. A JSAN issued in March 2015 on the 2013 Monitoring Report of the NDP determined that the NDP was satisfactorily implemented overall in 2013, representing a significant departure from the non-implementation of the first two poverty reduction strategies of 2003-2006 and 2008-2011.